Proyecto de evaluación de la producción y comercialización de arroz con productos orgánicos en la ciudad de Guayaquil - Vargas Romero, Jesús Alberto (2009)
In the present project realized a study about the production and commercialization of rice with organic products in the city of Guayaquil with its respective feasibility of market and financier, in the Property San Vicente of the Nobol town, which will provide to the objective market of the city of Guayaquil of a product of massive consumption as it is the produced rice of organic way with the purpose of offer a free healthy product of chemistries for benefit of our final consumer and avoid the injurious effects that the conventional production system causes, which with its continuous use contaminate the environment. With the implementation of this organic production system in the rice crop its will obtain satisfactory results for the producer as for the final consumer by their economic benefits, health and environment. The area in which one is going away to realize this organic production system that contemplates 100 hectares located in the Nobol town, being a strategic place for its production and commercialization towards the objective market, directed to people of upper middle and high class of Guayaquil city. Being of model or example for the other producers that are interested in adopt their crops a similar implementation, reducing therefore the negative impacts in the environment caused by the conventional production system. Also the commercialization of the product will be able possibly to be analyzed in the future organic rice to other cities of our country and to the international market. The study is based on the financial viability, of the costs related to its implementation and of the income that will obtain based in the market study.